Geoinformatics for Intelligent Transportation - Ivan, Igor; Benenson, Itzhak; Jiang, Bin; Horák, Jiří; Haworth, James; Inspektor, Tomáš (Lecture Notes in Geoinformation and Cartography,, 2015)
The aim of the book is to present and discuss new methods, issues and challenges involved in geoinformatics' contribution to making transportation more intelligent, efficient and human-friendly. It covers a wide range of topics related to transportation and geoinformatics. The themes are divided into four main sections: Transport modeling, Sensor data and services, Intelligent transport systems, and Transport planning and accessibility.